Workshop Penggunaan Moodle Bagi Guru SMA Negeri 1 Bangkinang Kota - Astuti; Sity Rahmy Maulidya; Hafizah Risali; Irfan Firdaus; Lina Suryani; Samsudin Duha; Sekedar Halawa (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
This workshop aims to improve the competency of teachers at SMA Negeri 1 Bangkinang Kota in utilizing Moodle as an online learning platform. Moodle was chosen because it is a popular and easily accessible Learning Management System (LMS), allowing teachers to create, manage and monitor learning processes more effectively. Workshop activities include a basic introduction to Moodle, course creation, management of teaching materials, and evaluation using the features available in Moodle. The methods used in this workshop are face-to-face training, simulations and direct practice using the Moodle platform. It is hoped that after attending this workshop, teachers will be more skilled in using Moodle to support teaching and learning activities at SMA Negeri 1 Bangkinang Kota, so that they can improve the quality of learning and adapt technology in the educational process.